YouTube as a Media for Developing English Proficiency: Experiments on Elementary School Students in Indonesia - Septian Maulana; Mega Febriani Sya; Annissa Mawardini; Yunianika, Ika Tri (Jurnal Pendidikan, 2023)
Technology continues to develop so that it causes changes in the pattern of human life without exception, also in education. This technological advancement requires teachers to develop and adjust additional competencies, one of which is using new technology in the learning process. Learning media can be interpreted as learning process aids that include subject matter information. This study aims to determine whether there is an influence of the use of YouTube videos on improving students' English learning outcomes. The method used in this study is a quantitative approach with a type of Quasi Experiment with a form of nonequivalent control group design. This research uses data analysis techniques, namely descriptive statistical analysis, analysis prerequisite tests, hypothesis tests, and n-gain analysis. The results of the hypothesis test in this study obtained the sig value. (2-tailed) 0.000 < 0.05. Thus, it can be concluded that Ha was accepted and Ho was rejected, this shows that the variables of YouTube video-based learning media have a significant effect on student English learning outcomes.